Digitalization and Optimization of HR at ONIP (DRC): An Integrated Mathematical Approach - Evariste Sindani; Simon Ntumba Badibanga; Pierre Kafunda Katalay; Eugène Mbuyi Mukendi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study proposes an integrated approach to digitalizing human resources (HR) in African public institutions by developing a performance optimization model. Based on five key variables—processing time, operational cost, service quality, degree of automation, and employee satisfaction—this model aims to enhance the overall efficiency of HR processes. The study is applied to the case of the National Office for Population Identification (ONIP) in the Democratic Republic of Congo and highlights substantial improvements in human resource management. Theoretically, the approach contributes to the digital transformation field through modeling, and practically, by offering a reproducible and adaptable framework for other public organizations with limited resources.Keywords: Digitalization, HR process optimization, ONIP, HR performance, HRIS.